(untitled) (International Journal of Food and Nutritional Sciences, 2022)
To transform is the act of crossing a boundary in the making of something new. The very first body that one changes are the first line one crosses in human existence, which is one’s mother’s body. This transformation happens for one’s selfishness. The mother’s body is always in transformation and is growing to accommodate the child. Emma Donoghue was born in Dublin, Ireland. Room is her seventh novel. It is based on the true story of the Fritzl case in Austria. It is narrated by a five-year-old Jack who lives in a twelve-foot shed that he shares with his mother. His prisoner is his biological father, Old Nick. This article focuses on the importance of child play, vocabulary and the power of transformation with the help of Freud’s ideas on Creative Writing and Daydreaming